2016
DOI: 10.1016/j.ijlp.2016.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Restraining good practice: Reviewing evidence of the effects of restraint from the perspective of service users and mental health professionals in the United Kingdom (UK)

Abstract: Safeguarding, balancing the concept of risk with the need for public protection and its implication for the lives of individuals, is an important facet of contemporary mental health care. Integral to safeguarding is the protection of human rights; the right to live free from torture, inhuman or degrading treatment, and having the right to liberty, security, respect and privacy. Professionals are required to recognise all of these rights when delivering care to vulnerable people. In the United Kingdom (UK) ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 23 publications
1
28
0
3
Order By: Relevance
“…Good mental health nursing is predicated on therapeutic partnerships between service users and staff (Warne & McAndrew ), with good communication and interpersonal skills having the potential to prevent or minimize the need for restraint (Cusack et al . ). In the light of this and the evidence presented in this study, mental health nurses are well positioned to use their skills and knowledge positively to promote therapeutic engagement and eradicate physical restraint.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Good mental health nursing is predicated on therapeutic partnerships between service users and staff (Warne & McAndrew ), with good communication and interpersonal skills having the potential to prevent or minimize the need for restraint (Cusack et al . ). In the light of this and the evidence presented in this study, mental health nurses are well positioned to use their skills and knowledge positively to promote therapeutic engagement and eradicate physical restraint.…”
Section: Discussionmentioning
confidence: 97%
“…For some time, progressive and critical service users have expressed concerns about the legitimacy and potentially harmful impact of coercion and restrictive practices (Cusack et al . ; Duxbury ; McKeown et al . ; Rose et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviewing evidence of the effects of restraint, Cusack et al ( 2016 ) concluded that ‘restraint can be a form of abuse, its inappropriate use often being a consequence of fear, neglect and lack of using de-escalation techniques’.…”
Section: Industrialised Westmentioning
confidence: 99%
“…As mentioned in this chapter's clinical vignette, restraints may not eliminate the risk of DSH. Therefore, the choice to use PhyR continues to be controversial and should only be entertained as a last resort option when there exists a real possibility of serious physical injury to self or others [63][64][65]. There is therefore a need for caution and balanced judgment on part of the treatment team, beginning with a well-informed understanding of potential complications and safety procedures designed to prevent adverse outcomes [63][64][65].…”
Section: Physical Restraintsmentioning
confidence: 99%